Expanding the structure–activity relationship of sulfoxaflor: the synthesis and biological activity of N‐heterocyclic sulfoximines1. Issue 7 (10th September 2014) - Nugent, Benjamin M; Buysse, Ann M; Loso, Michael R; Babcock, Jon M; Johnson, Timothy C; Oliver, M Paige; Martin, Timothy P; Ober, Matthias S; Breaux, Nneka; Robinson, Andrew; Adelfinskaya, Yelena
Abstract BACKGROUND Sulfoxaflor, a new insect control agent developed by Dow AgroSciences, exhibits broad‐spectrum control of many sap‐feeding insect pests, including aphids, whiteflies, leafhoppers, planthoppers and lygus bugs. During the development of sulfoxaflor, structure–activity relationship (SAR) exploration of the sulfoximine functional group revealed that the nature of the sulfoximine nitrogen substituent significantly affects insecticidal acitivity. As part of the investigation to probe the various electronic, steric and lipophilic parameters at this position, a series of N‐heterocyclic sulfoximines were synthesized and tested for bioactivity against green peach aphid. RESULTS Using a variety of chemistries, the nitrile substituent was replaced with different substituted five‐ and six‐membered heterocycles. The compounds in the series were then tested for insecticidal acitivty against green peach aphid in foliar spray assays. In spite of the larger steric demand of these substituents, the resulting N‐heterocyclic sulfoximine analogs displayed good levels of efficacy. In particular, the N‐thiazolyl sulfoximines exhibited the greatest activity, with LC50 values as low as 1 ppm. CONCLUSIONS The novel series of N‐heterocyclic sulfoximines helped to advance the current knowledge of the sulfoxaflor SAR, and demonstrated that the structural requirement for the sulfoximine nitrogen position was not limited to small, electron‐deficient moeities, but rather was tolerant of larger functionality. © 2014 Society of Chemical Industry